2017
DOI: 10.18632/oncotarget.19674
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing reveals novel mutations and epigenetic regulation in hypopharyngeal carcinoma

Abstract: Hypopharyngeal cancer (HPC) frequently presents at an advanced stage, resulting in poor prognosis. Although combined surgical therapy and chemoradiotherapy have improved the survival for patients with HPC over the past 3 decades, the mortality rate in late-stage diagnosis of HPC is unsatisfactory. In this study, we performed whole-exome sequencing (WES) of 23 hypopharyngeal tumor and paired adjacent normal tissue to identify novel candidate driver genes associated with hypopharyngeal carcinoma. We identified s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…To further support the tumor suppressor role of this gene, induced overexpression of REC8 in gastric cancer inhibited proliferation, invasion and migration of gastric cancer cells, while the knockdown of REC8 reversed these effects in vitro [147]. Not surprisingly, studies revealed that REC8 is epigenetically downregulated in gastric cancer [148], thyroid cancer [149] and gastrointestinal stromal tumors [150] and mutated in hypopharyngeal [151], and ovarian carcinomas [152].…”
Section: Cohesins Oncogenes Tumor Suppressors and Transcriptional Repression In Cancersmentioning
confidence: 99%
“…To further support the tumor suppressor role of this gene, induced overexpression of REC8 in gastric cancer inhibited proliferation, invasion and migration of gastric cancer cells, while the knockdown of REC8 reversed these effects in vitro [147]. Not surprisingly, studies revealed that REC8 is epigenetically downregulated in gastric cancer [148], thyroid cancer [149] and gastrointestinal stromal tumors [150] and mutated in hypopharyngeal [151], and ovarian carcinomas [152].…”
Section: Cohesins Oncogenes Tumor Suppressors and Transcriptional Repression In Cancersmentioning
confidence: 99%
“…3 One important reason is that after the treatments up to 30% of patients with HSCC die within a year as a result of distant metastasis, which makes it a particularly devastating disease. 4 Although there have been some studies on the pathogenesis of HSCC, [5][6][7] investigations of new potential mechanisms related to the development and progression of HSCC are still urgent.…”
Section: Introductionmentioning
confidence: 99%
“…Most variants were detected in chromosomes 1, 17 and 19, which are consistent with regional changes detected previously in meningiomas [ 11 , 31 ]. Similar to other tumours, the most common variants here were missense mutations, with a C > T transversion in the exomic regions [ 32 , 33 , 34 ]. Tri-homozygosity among variants detected in the BTCs were very rare, and only 16 variants showed a heterozygous pattern in the blood, along with a homozygous change in the tumour or cell line.…”
Section: Discussionmentioning
confidence: 61%